2015
DOI: 10.1051/0004-6361/201526620
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing solar magnetic fields from historical observations

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full DRO policy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
58
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 50 publications
5
58
0
Order By: Relevance
“…Thus this area-scaled butterfly diagram provides some additional information for a greater time-span (1907-2007), in contrast to the super synoptic map presented in Sheeley et al (2011) with a study period between 1915 and 1985. The location pf overlap between the plage structures and magnetic patches in turn validated the theoretical expectation of a higher field strength being correlated with less Ca II K absorption (Pevtsov et al 2016). Therefore, the century-long Ca II K data can act as a proxy for understanding the locational evolution of magnetic patches.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…Thus this area-scaled butterfly diagram provides some additional information for a greater time-span (1907-2007), in contrast to the super synoptic map presented in Sheeley et al (2011) with a study period between 1915 and 1985. The location pf overlap between the plage structures and magnetic patches in turn validated the theoretical expectation of a higher field strength being correlated with less Ca II K absorption (Pevtsov et al 2016). Therefore, the century-long Ca II K data can act as a proxy for understanding the locational evolution of magnetic patches.…”
Section: Resultssupporting
confidence: 66%
“…Recently Pevtsov et al (2016) have attempted to create a homogeneous, long term series of pseudomagnetograms using a combination of Ca II K line images and sunspot polarity measurements. We hope to pursue the same in the near future for our KSO data.…”
mentioning
confidence: 99%
“…The issue of the low spatial resolution of the Ca 854.2 nm line was mentioned by Pevtsov et al (2016) based on the findings of Leenaarts et al (2006). The reported reversal of the relation at high magnetic fluxes with the Ca II K data, as well as the lack of correlation for the Ca II infrared data considered by Pevtsov et al (2016), is perfectly consistent with the inclusion of sunspots in their analysis. The large scatter is possibly due to the narrower nominal bandwidth of Mt Wilson data (0.35 Å) compared to that of the Rome/PSPT (2.5 Å).…”
Section: Comparison To Results From the Literaturementioning
confidence: 76%
“…Schrijver & Harvey (1989) also derived an integrated chromospheric emission from low-resolution synoptic maps and concluded that power laws describing local relationships led to similar power laws describing the so-called flux-flux (between disk-integrated variables) relationships. Conversely, Pevtsov et al (2016) used Ca synoptic maps to reconstruct pseudo-magnetograms.…”
Section: Observational Inputsmentioning
confidence: 99%